A new hybrid multiaxial fatigue life model based on critical plane continuum damage mechanics and genetic algorithm - Masood, Kamal (2015)
Multiaxial fatigue is one of the most common failure mechanisms encountered by the mechanical components during service life. For reliability assessment of the components under real-life service conditions, and maintenance, the understanding of multiaxial fatigue phenomenon is essential. Despite extensive research in this area, the fatigue life prediction is still a challenging task. The application of analytical and numerical methods in fatigue life analysis under real-life service conditions is becoming more significant, given the time and costs considerations in experimental testing. This study aims to develop a hybrid multiaxial fatigue model capable of estimating fatigue life independent of applied loading-path-shape with the application of the most commonly available material property. A new fatigue parameter is formulated based on stress-strain variables identified from various fatigue life models in order to deal with mean stress effects and non-proportional hardening. Continuum damage mechanics approach is applied to develop damage expression as a continuously damage-accumulative function in terms of fatigue parameter. Genetic algorithm is also applied for the calibration of proposed model in terms of calibrated coefficients. The developed hybrid model is calibrated using complex profiles for proportional and non-proportional loading under in-phase and out-of-phase loading conditions. The model is validated against the published experimental results under various loading and material conditions including SS304, carbon steel C40, EN3B, Steel20 and Titanium alloy BT9. Interpolation scheme for calibrated model coefficients is applied for loading cases with same profiles and different magnitude. For in-phase and out-of-phase loading with zero and positive mean stress the proposed model provides good correlation with experimental data (min. 4% diff.) for C40, EN3B and Steel 20. For SS304 predicted fatigue life from proposed model for complex profiles, calibrated with characteristic profiles, correlates well with the experimental data with an agreeable difference (min.6%). The results of the proposed model for Titanium alloy BT9 and steel 20 with block loading correlates reasonably well with experimental data (min. 4-10% diff.). The proposed model serves as path-independent fatigue life estimating tool hence can be used with any type of loading conditions. The notion of characteristic profiles for the calibration of the model is also coherent with the application of equivalent fatigue loading in generating experimental data for calibration. The model is simple in application with the use of genetic algorithm for model calibration making use of only the material fatigue limit. Thus the proposed model is more accurate for variety of loading and material conditions. The hybrid approach of critical plane, continuum damage mechanics and calibration through genetic algorithm provided a strong basis for a universally accepted multiaxial fatigue life model. Interpolation scheme based on the multiaixality of stresses is suggested for the determination of coefficients of the model for different loading paths. Material parameter including stress sensitivity factor for normal or shear stress can be incorporated to improve the calibration process. The proposed model can serve as an efficient tool for multiaxial fatigue life analysis in academics as well as commercial applications, especially automotive and aircraft industry, due to inherent flexibility of the model for accommodating different loading conditions.